Evaluasi Program Pendidikan Guru Penggerak dalam Meningkatkan Pembelajaran Berdiferensiasi di SMK Negeri 1 Tapaktuan Kabupaten Aceh Selatan - Vetta Darmi Yetti; Lili Kasmini; Akmaluddin Akmaluddin (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This research aims to This research aims to evaluate the driving teacher education program in improving differentiated learning at the State Vocational High School 1 Tapaktuan, South Aceh Regency. This research uses a qualitative approach, with phenomenological research methods. The data collection techniques used in this research are observation, interviews and documentation. The data analysis technique uses stages of data reduction, data presentation, and drawing conclusions/verification. Based on the research results, it is known that the Activator Teacher's planning in improving differentiated learning at the Tapaktuan 1 State Vocational High School, South Aceh Regency has been going well, as evidenced by the Activator Teacher's planning in improving differentiated learning at the Tapaktuan 1 State Vocational School, South Aceh Regency and the use of Need Assessment in differentiated learning at State Vocational High School 1 Tapaktuan, South Aceh Regency, guided by the evaluation concept of the Context, Input, Process and Product model.